Fourteen talks by age fourteen : the essential conversations you need to have with your kids before they start high school - and how (best) to have them - Icard, Michelle (Harmony Books, 2020)
"The fourteen essential conversations to have with your tween and early teenager to prepare them for the emotional, physical, and social challenges ahead, including scripts and advice to keep the communication going and stay connected during this critical developmental window." -- Amazon.com.